(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
Modern Technology is a basic tool that can be used in communicating with others worldwide. It is commonly used in our generation. Especially on teenagers, they use technology to easily search and to enhance their daily lives by reading the information on the internet. Because of the continuous use of technology, students learn more and it helps teachers to explain each subject properly and in detail, affecting the students’ performances. Technology helps but, in some ways, it also has a disadvantage if it is overused. This study aims to assess the effects of using modern technology in the learning skills of grade 12 ABM students and address its negative effects. The qualitative method was used in the study. Descriptive design was used in the assessment of the Effects of Modern Technology in the Learning Skills of Grade 12 students. Four variables were affected by Modern Technology such as Reading Skills, Writing Skills, Communication Skills, and Creative Skills. The data were gathered using questionnaires. The results of this study revealed that modern technology affects the Learning Skills of the Grade 12 ABM students in terms of the following variables. (1) Reading Skills -It affects their learning by helping them be more efficient readers and become aware in society through reading. (2) Writing Skills –It gives them the correct words and grammar to improve their writings. (3) Communication Skills –It helps them to communicate easily about their tasks and to share their thoughts and information with others. (4) Creative Skills –It widens their abilities in researching specific studies. The results demonstrate the need for the teachers and school administrators to always monitor the students and be familiar with the technology they are using. Also, they should always remind them that too much technology use can affect them that is why they must be reminded of their limitations. Parents and teachers must remind them that abusing technology can put them in harm or danger. With these, they can avoid wrong information from spreading on the internet, making them wiser in seeking the information needed.